PERILAKU DETEKSI DINI PENYAKIT TIDAK MENULAR PADA DOSEN DI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Wati, Ida Ayu Sri Puspita; Sari, Ayu Kartika; Lubis, Dinar (ARCHIVE OF COMMUNITY HEALTH, 2019)
ABSTRACT One of the models applied by Denpasar City in waste management is the 3R Integrated Waste Management Site (TPST-3R) in Kesiman Kertalangu Village, Denpasar City. Some obstacles to the implementation of waste management at TPST-3R such as the lack of community participation in waste management. The purpose of this study was to determine the factors that influence the level of community participation in waste management in TPST-3R in Kesiman Kertalangu Village, Denpasar. The design of this study used analytic observational research, using a quantitative approach with a cross sectional design. The place of this study was in TPST-3R in Kesiman Kertalangu Village, Denpasar City, the sample size in this study was 84 heads of households. The results showed that the proportion of community participation in waste management was 38.10%. Factors that significantly influence community participation on waste bank are community knowledge and support from the community leaders (OR = 7.76; 95% CI = 2.19-27.58; p = 0.002) and (OR = 20.26; 95% CI = 5.10-, respectively. Keywords: Waste management, waste bank, level of participation.